2018
DOI: 10.3389/fpsyg.2018.01466
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Academics: A Model for Simultaneously Advancing Campus-Based Supports for Learning Disabilities, STEM Students’ Skills for Self-Regulation, and Mentors’ Knowledge for Co-regulating and Guiding

Abstract: Learning disabilities are highly prevalent on college campuses, yet students with learning disabilities graduate at lower rates than those without disabilities. Academic and psychosocial supports are essential for overcoming challenges and for improving postsecondary educational opportunities for students with learning disabilities. A holistic, multi-level model of campus-based supports was established to facilitate culture and practice changes at the institutional level, while concurrently bolstering mentors’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…We found that effective strategy use across life’s contexts was critical to self-managing as a young person in college who is transitioning to adulthood with a chronic neurodevelopmental condition. This finding is consistent with research reporting the essential nature of executive skills to college success for those with LD/ADHD; critical executive skills include planning, goal setting, organization, flexibility, time management, and structuring time and tasks [23]. For our participants, the transition to adult roles involved simultaneously learning to cope with time and productivity challenges while also learning to self-manage LD/ADHD-related health, role, social, and emotional concerns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that effective strategy use across life’s contexts was critical to self-managing as a young person in college who is transitioning to adulthood with a chronic neurodevelopmental condition. This finding is consistent with research reporting the essential nature of executive skills to college success for those with LD/ADHD; critical executive skills include planning, goal setting, organization, flexibility, time management, and structuring time and tasks [23]. For our participants, the transition to adult roles involved simultaneously learning to cope with time and productivity challenges while also learning to self-manage LD/ADHD-related health, role, social, and emotional concerns.…”
Section: Discussionsupporting
confidence: 88%
“…This paper reports on a secondary data analysis. Data were transcripts from group discussions and individual interviews that were collected as part of a larger study, which developed and tested a campus-based model of holistic LD/ADHD supports [23]. The data were originally collected for the purpose of gaining actionable insights into the participants’ needs and experiences as emerging young adults with LD/ADHD within a college environment.…”
Section: Methodsmentioning
confidence: 99%
“…Journal reflections showed an increase in the application of UDL strategies in trying to make better class materials and using different teaching methods to engage all students in the lessons (Moon et al, 2011). Kreider et al (2018) researched the benefits of the Comprehensive Support for STEM Students with Learning Disabilities (CS 3 LD), a campus-based framework for supporting students with disabilities. The CS 3 LD model supports students with learning disabilities (LD) at three different levels, institutional, personal, and interpersonal.…”
Section: Review Of Research Udi/udl In Educationmentioning
confidence: 99%
“…The model also focused on the student's health and well-being. Kreider et al (2018) utilized a mixed-methods design for their 4-year project. Qualitative data consisted of focus group discussions, participant communications, and individual interviews.…”
Section: Review Of Research Udi/udl In Educationmentioning
confidence: 99%
“…In our opinion, the competence approach is not universal. On the one hand, in recent years much attention has been paid to the role of universities, taking into account not only their educational function [10,11]. On the other hand, the role and functions of education are changing constantly, since in the era of rapid information deterioration, the most important function of education is the formation of appropriate cognitive structures providing perception and information processing.…”
Section: B Algebraic Approach To Knowledge-intensive Activitiesmentioning
confidence: 99%